Two Types of Phytases (Histidine Acid Phytase and β-Propeller Phytase) in Serratia sp. TN49 from the Gut of Batocera horsfieldi (Coleoptera) Larvae - Rui Zhang; Peilong Yang; Huoqing Huang; Pengjun Shi; Tiezheng Yuan; Bin Yao (Current Microbiology, 2011)

Induction of DIMBOA accumulation and systemic defense responses as a mechanism of enhanced resistance of mycorrhizal corn (Zea mays L.) to sheath blight - Yuan Yuan Song; Man Cao; Li Jun Xie; Xiao Ting Liang; Ren Sen Zeng; Yi Juan Su; Jing Hua Huang; Rui Long Wang; Shi Ming Luo (Mycorrhiza, 2011)

How Human Household Size Affects the Habitat of Black-and-White Snub-Nosed Monkeys (Rhinopithecus bieti) in Hongla Snow Mountain Nature Reserve in Tibet, China - Rui-Chang Quan; Yong Huang; Matthew W. Warren; Qi-Kun Zhao; Guopeng Ren; Sheng Huo; Yongcheng Long; Jianguo Zhu (International Journal of Primatology, 2011)

Age-dependent expression of forkhead box O proteins in the duodenum of rats - Pan Huang; Zhen-qi Zhou; Rui-hua Huang; Bo Zhou; Quan-wei Wei; Fang-xiong Shi (Journal of Zhejiang University-SCIENCE B, 2011)

Identification of a Novel Bacterial K+ Channel - Guanghua Tang; Bo Jiang; Yuan Huang; Ming Fu; Lingyun Wu; Rui Wang (The Journal of Membrane Biology, 2011)

Expression of a novel gene FAM43B repressing cell proliferation is regulated by DNA methylation in hepatocellular carcinoma cell lines - Xiao Xu; Rui-Fang Liu; Bing-Bing Wan; Wen-Ming Xing; Jian Huang; Ze-Guang Han (Molecular and Cellular Biochemistry, 2011)

A study on the effects of the surrounding faults on water loss in the Zoige Wetland, China - Mei Li; Rui Xu; Wendian Huang; Hailong Sun; Lin Luo (Journal of Mountain Science, 2011)

A new bioorganic fertilizer can effectively control banana wilt by strong colonization with Bacillus subtilis N11 - Nan Zhang; Kai Wu; Xin He; Shu-qing Li; Zhen-hua Zhang; Biao Shen; Xing-ming Yang; Rui-fu Zhang; Qi-wei Huang; Qi-rong Shen (Plant and Soil, 2011)

Production of Chitinase and its Optimization from a Novel Isolate Serratia marcescens XJ-01 - Jin-Lan Xia; Jing Xiong; Rui-Yong Zhang; Ke-Ke Liu; Bin Huang; Zhen-Yuan Nie (Indian Journal of Microbiology, 2011)

Viral proteomics: The emerging cutting-edge of virus research - ShengTao Zhou; Rui Liu; Xia Zhao; CanHua Huang; YuQuan Wei (Science China Life Sciences, 2011)

Localized Delivery of Antisense Oligonucleotides by Cationic Hydrogel Suppresses TNF-α Expression and Endotoxin-Induced Osteolysis - Lei Dong; Zhen Huang; Xing Cai; Jiawei Xiang; Yi-An Zhu; Rui Wang; Jiangning Chen; Junfeng Zhang (Pharmaceutical Research, 2011)

The role of diurnal cycle in subduction/obduction - Ling Ling Liu; Rui Xin Huang; Fan Wang (Journal of Oceanography, 2011)

Estimate of eddy energy generation/dissipation rate in the world ocean from altimetry data - Chi Xu; Xiao-Dong Shang; Rui Xin Huang (Ocean Dynamics, 2011)

Effect of hypoxia on immunological, physiological response, and hepatopancreatic metabolism of juvenile Chinese mitten crab Eriocheir sinensis - Renjie Qiu; Yongxu Cheng; Xuxiong Huang; Xugan Wu; Xiaozhen Yang; Rui Tong (Aquaculture International, 2011)

Diversity, abundance and characterization of ruminal cysteine phytases suggest their important role in phytate degradation - Huoqing Huang; Rui Zhang; Dawei Fu; Jianjie Luo; Zhongyuan Li; Huiying Luo; Pengjun Shi; Peilong Yang; Qiyu Diao; Bin Yao (Environmental Microbiology, 2011)
Summary A novel class of cysteine phytase showing ability to degrade phytate has recently been isolated from rumen bacteria. To expand our knowledge of this enzyme class, a total of 101 distinct cysteine phytase gene fragments were identified from the ruminal genomic DNA of Bore goats and Holstein cows, and most of them shared low identities (

The emplacement mechanisms and growth styles of the Guposhan-Huashan batholith in western Nanling Range, South China - ZuoHai Feng; ChunZeng Wang; JinCheng Liang; JunZhao Li; YongGao Huang; JiaFei Liao; Rui Wang (Science China Earth Sciences, 2011)